Correction: Su et al. Underwater Ionic Current Signal Sensing and Information Transmission by Contact-Induced Charge Transfer. Appl. Sci. 2025, 15, 2846 - Boru Su; Junyan Zhang; Yunfei Deng; Lin Chi (Applied Sciences)
In the original publication [...]